Ortaokul Türkçe ders kitaplarındaki metinlerin PISA ölçütünde metinsellik özelliklerine göre incelenmesi - Evci, Büşra (My University, 2021)
Araştırmada PISA ölçütünde metinsellik özellikleri tespit edilmiş ve ortaokul (5-8. sınıf) Türkçe ders kitaplarındaki metinlerin bu özellikleri taşıma durumları incelenmiştir. Araştır-ma nitel araştırma metodolojisine uygun olarak desenlenmiş ve veriler doküman incelemesi yöntemi kullanılarak elde edilmiştir. Araştırma nesnesini 2019-2020 eğitim ve öğretim yılında okutulan ortaokul (5-8. sınıf) Türkçe ders kitaplarındaki PISA’nın “sürekli metin” kategorisinde değerlendirilebilecek 99 okuma metni oluşturmuştur. İncelenen metinler “ölçüt örnekleme yöntemi”ne uygun olarak seçilmiştir. Türkçe Dersi Öğretim nda (2019) Türkçe ders kitaplarına alınacak metinlerin niteliklerini açıklayan 14 maddeden 2’si metnin anlam boyutuna yöneliktir. Bu araştırmada buna ek olarak PISA raporlarında yer alan iki temel ölçüt olan okuma bilişsel süreçleri ve yeterlik düzeylerinden hereketle “bilgi aktarımı, başlık içerik uyumu, ipuçlarının kullanımı, ana düşüncenin ifade edilişi, yardımcı düşüncelerin kullanımı, metnin yazılış amacı, farklı bakış açılarının kullanılması ve farklı bilişsel becerilerin harekete geçirilmesi” olmak üzere sekiz başlık altında PISA ölçütünde metinsellik özellikleri tanımlanmıştır.Araştırma nesnesi araştırmacı tarafından geliştirilen “PISA Ölçütünde Metinsellik Rubriği (PÖMR)” yardımıyla çözümlenmiştir. Araştırma sonucuna göre PISA ölçütünde metinsellik özelliklerini ortaokul (5-8. sınıf) Türkçe ders kitaplarında incelenen 99 okuma metninin 67’si yeterli, 29’u orta ve 3’ü yetersiz düzeyde taşımaktadır. PÖMR’den aldıkları puana göre 5. sınıf Türkçe ders kitabındaki 11 metin (x̄ = 10,52), 6. sınıf Türkçe ders kitaplarındaki 10 metin (x̄ =11,8), 7. sınıf Türkçe ders kitaplarındaki 13 metin (x̄ = 12,11), 8. sınıf Türkçe ders kitabındaki 8 metin (x̄ = 11,22) ortalama puanın altında kalmıştır. PISA ölçütünde metinsellik özelliklerinin ortaokul (5-8. sınıf) Türkçe ders kitaplarında en iyi düzeyde temsil edildiği sınıf seviyesi 7. sınıf, en kötü düzeyde temsil edildiği sınıf seviyesi 5. sınıftır. PISA ölçütünde metinsellik özelliklerinden “ana düşünce” alt ölçütü ders kitaplarında en iyi düzeyde temsil edilmiş, “farklı bakış açıları” alt ölçütü en kötü düzeyde temsil edilmiştir. Araştırmada Türkçe ders kitaplarına metin seçme kriterlerine PISA ölçütünde metinsellik özelliklerinin de eklenmesi önerilmiştir.

In the study conducted, the textuality characteristics of the PISA criteria were de-termined, and then it was examined whether the texts in middle school (5th-8th grade) Turkish textbooks presented these characteristics. The study was conducted in accordance with qualitative research methodology, and data was collected using the document review method. The object of the study consisted of 99 reading texts studied in the 2019-2020 academic year in middle school (5th-8th grade) Turkish textbooks, which can be evaluated in PISA's continuous text category. The texts examined are selected in accordance with the criteria sampling method. In the Turkish Language Curriculum (2019), 2 out of the 14 articles stating the qualities of the texts to be included in Turkish textbooks are aimed at the meaning dimension of the text. In addition to this, based on the reading cognitive pro-cesses and competence levels, which are the two primary criteria included in PISA reports, in this study, the textuality characteristics in the PISA criteria were identified under eight headings: information transfer, title-content compliance, expression of main idea, use of auxiliary thoughts, purpose of text, use of different perspectives, and activation of diffe-rent cognitive skills. The object of the study was resolved by employing the Textuality Rubric in PISA Criteria (PÖMR), which was developed by the researcher. According to the result of the study, of the 99 reading texts examined in middle school (5th-8th grade) Turkish textbooks, 67 feature adequate textual characteristics in the PISA criteria, while 29 are moderate and 3 are insufficient. According to their PÖMR score, 11 texts in the 5th grade Turkish language textbooks (x̄ = 10.52), 10 texts in the 6th grade Turkish language textbooks (x̄ =11.8), 13 texts in the 7th grade Turkish language textbooks (x̄ = 12.11), and 8 texts in the 8th grade Turkish language textbook (x̄ = 11.22) were below the average sco-re. The grade level in which the textuality characteristics in the PISA criteria are best repre-sented in middle school (5th-8th grade) Turkish language books is the 7th grade, while it is represented the worst at the 5th grade level. Among the textuality characteristics in the PISA criteria, “main idea” is the sub-criteria best represented in the textbooks, while “dif-ferent perspectives” is the worst represented sub-criteria. The study also suggests including the textuality characteristics in the PISA criteria to the text selection criteria for Turkish textbooks.
Keywords: analitik rubrik Reading skills; analytical rubric; Ders kitapları; metinsellik özellikleri; Middle school teaching; okuma becerileri; Ortaokul öğretimi; Öğrenim ve öğretim; PISA; Study and teaching; Textbooks; textuality characteristics; Turkish language; Türk dili